Comparative efficacy of Chinese herbal injections for treating chronic heart failure: a network meta-analysis - Kai-Huan Wang; Jia-Rui Wu; Dan Zhang; Xiao-Jiao Duan; Meng-Wei Ni (BMC, 2018)
Abstract Background On account of deterioration of chronic heart failure (CHF) and extensive exploration of Chinese herbal injections (CHIs), we performed a network meta-analysis to investigate the efficacy of CHIs (Huangqi injection, Shenfu injection, Shengmai injection, Shenmai injection, Shenqi Fuzheng injection, Yiqifumai injection) on the basis of western medicine (WM) treatment in CHF. Methods Literature search was conducted in Embase, the Cochrane Library, Pubmed, Chinese Biological Medicine Database, China National Knowledge Infrastructure, Wanfang Database, Chinese Scientific Journal Database from inception to June 12nd 2017, and study selection was abided by a prior eligible criteria. Results Ultimately, a total of 113 randomized controlled trials (RCTs) were enrolled. The clinical data of the effective clinical rate, left ventricular ejection fraction, cardiac output and others outcomes was estimated by Stata software and Winbugs software. Risk of bias was assessed by Cochrane Collaboration's tools. Integrating the each outcome's results, a combination of Shengmai injection/Shenmai injection and WM obtain a first rank in most outcomes, particularly primary outcomes. Conclusions In conclusion, on the basis of WM, Shengmai injection or Shenmai injection may be a perforable treatment in CHF. In terms of insufficient of this study, more high quality RCTs needed to implement to support our conclusions.